Plasticity of electric organ discharge waveform in the South African Bulldog fish, Marcusenius pongolensis: tradeoff between male attractiveness and predator avoidance? - Hanika, Susanne; Kramer, Bernd (Frontiers in zoology, 2008)
In adult male Marcusenius pongolensis the duration of their Electric Organ Discharge (EOD) pulses increases with body size over lifetime (267 to 818 mus, field-measured). Spawning males have been observed to exhibit an additional, temporary pulse duration increase which probably betters their mating success but increases predation risk by electroreceptive catfish. We here study the question of how the additional pulse duration increase is triggered and for how long it persists, in an attempt to understand the compromise between opposing selective forces. Here, we demonstrate short-term plasticity in male EOD waveform in 10 captive M. pongolensis. An increase in EOD duration was experimentally evoked in two different ways: by exchanging the familiar neighbours of experimental subjects for stranger males that were separated by plastic mesh partitions, or by separating familiar fish by plastic mesh partitions introduced into their common tank. Both treatments evoked an increase of male EOD duration. Values exceeded those found in the non-reproductive season in nature. In one male the increase of EOD duration was 5.7 fold, from 356 mus to 2029 mus. An increase in EOD duration was accompanied by a high level of aggression directed against the neighbours through the plastic mesh. With conditions remaining constant, EOD duration receded to 38 - 50% of the maximum EOD duration after 10 weeks, or, more rapidly, when sensory contact between the fish was severely restricted by the introduction of a solid plastic wall. The short-term increase of EOD duration evoked by experimental manipulation of sensory contact with conspecifics through the plastic mesh, as reported here, resembled the changes in EOD waveform that accompanied reproduction in two captive males. Plasticity of the male EOD in pulse duration seems to be an adaptation for (1) securing a higher fitness by a sexually "attractive" long-duration EOD, while (2) limiting the risk of detection by electroreceptive predators, such as the sharptooth catfish, by receding to a shorter EOD as soon as reproduction is over.